2021
DOI: 10.1136/practneurol-2019-002341
|View full text |Cite
|
Sign up to set email alerts
|

Localisation in focal epilepsy: a practical guide

Abstract: The semiology of epileptic seizures reflects activation, or dysfunction, of areas of brain (often termed the symptomatogenic zone) as a seizure begins and evolves. Specific semiologies in focal epilepsies provide an insight into the location of the seizure onset zone, which is particularly important for presurgical epilepsy assessment. The correct diagnosis of paroxysmal events also depends on the clinician being familiar with the spectrum of semiologies. Here, we summarise the current literature on localisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“… 7 There is often dissociation between the topography of IEDs and the SOZ, and it is generally recognized that the IZ is larger than the SOZ. 8 , 9 IZs could extend to brain regions much larger than the SOZ as well as to spatially distant sites where seizures may jump to non-adjacent leads during propagation. The clinical significance of the analysis presented in this manuscript is that IEDs can be used to identify the SOZ.…”
Section: Commentarymentioning
confidence: 99%
“… 7 There is often dissociation between the topography of IEDs and the SOZ, and it is generally recognized that the IZ is larger than the SOZ. 8 , 9 IZs could extend to brain regions much larger than the SOZ as well as to spatially distant sites where seizures may jump to non-adjacent leads during propagation. The clinical significance of the analysis presented in this manuscript is that IEDs can be used to identify the SOZ.…”
Section: Commentarymentioning
confidence: 99%
“…The direction of associations between nodes formed in areas of the brain during epileptic seizures is still an unresolved issue (Colmers and Maguire, 2020 ; Gil et al, 2020 ; Chowdhury et al, 2021 ). This study aimed to address the problem and provide information in agreement with Tracy et al ( 2021 ), showing that basal and infusion time slices present a different pattern of communication than that observed during MYO and GTCS time slices.…”
Section: Discussionmentioning
confidence: 99%
“…The direction of associations between nodes formed in areas of the brain during epileptic seizures is still an unresolved issue (Colmers and Maguire, 2020 ; Gil et al, 2020 ; Chowdhury et al, 2021 ). Tracy et al ( 2021 ) showed that it could change while such seizures occur.…”
Section: Introductionmentioning
confidence: 99%
“…Video-EEG is an essential part of identifying these zones and requires a thorough understanding of seizure semiology. Further detail on presurgical evaluation is beyond the scope of this article but covered more in-depth elsewhere 8 15…”
Section: Discussionmentioning
confidence: 99%
“…Ictal-onset EEG patterns and semiology can differ due to various network connections within and between different brain areas; consequently, these might not reflect the precise origin of the seizure, especially when there is rapid propagation. It is therefore important to be aware of various patterns of propagation 8. Accurate recognition of seizure patterns not only leads to correct epilepsy classification and management, but also helps to avoid misdiagnosis, in particular of dissociative seizures.…”
Section: Introductionmentioning
confidence: 99%